Effect of fiber heat treatment on microstructure and mechanical properties of 2.5D T700 carbon fiber reinforced SiC composites. (31st October 2018) - Liao, Jiahao; Chen, Zhaofeng; Li, Binbin; Wang, Yang; Yu, Shenjie; Guan, Tianru; Yuan, Xiaosen; Liu, Jiabao; Tang, Kaiyuan; Cui, Sheng
Abstract: T700 carbon fibers were heat treated at 1300 °C and 1600 °C to investigate the effect on microstructure of pyrolytic carbon (PyC) interphase and mechanical properties of 2.5D T700 carbon fiber reinforced SiC (2.5D C f /SiC) composites, and the untreated carbon fiber acts as a comparison. The flexural strength was measured using three-point bending test and the fracture toughness was evaluated by a single-edge notched beam test. Results show that heat treatment at 1300 °C leads to highest mechanical properties of 2.5D C f /SiC composites, with the flexural strength in warp direction of 248.6 ± 12.3 MPa, the flexural strength in weft direction of 421.6 ± 15.1 MPa, and the fracture toughness of 18.7 ± 1.7 MPa · m 1/2 . Nevertheless, both the unheated and heat treatment at 1600 °C result in a decrease in mechanical properties. The microstructural investigations revealed that the bonding strength between the carbon fiber and PyC is best when the heat treatment of carbon fiber at 1300 °C.